Pengaruh Kinerja Keuangan pada Belanja Daerah dan Pertumbuhan Ekonomi dan Implikasinya Pada Indeks Pembangunan Manusia - Dwiyandari, Luh Dini Yasintha; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 22 No 3 (2018), 2018)
Increasing Human Development Index, the accuracy of local expenditure allocation and high economic growth is a picture of government performance in the prosperity of its people. The achievement of human development goals reflected in Human Development Index is highly dependent on government commitment as a provider of supporting facilities. Improved financial performance, allegedly not always able to encourage economic growth, as well as the accuracy of local expenditure allocations and improvement of the Human Development Index. This study aims to determine the effect of regional financial performance on economic growth and regional spending on the Human Development Index. The sample in this research are 8 regencies and 1 city in Bali Province with research object that is regional finance performance, regional expenditure, economic growth, and Human Development Index year 2011-2015. Sample determination was done by using nonprobability method and saturated sampling technique. This research uses multiple linear regression analysis technique. The results show that financial performance has no effect on economic growth, while financial performance has a positive effect on regional expenditure and human development index. The test results also show that economic growth has no effect on the human development index but local spending has a positive effect on the human development index. The results of mediation testing indicate that regional expenditure is able to mediate the relationship between financial performance on the human development index, while economic growth can not mediate the effect of local financial performance on human development index. Keywords : Financial performance, economic growth, regional spending, human development index